A STRUCTURAL EQUATION MODEL OF THE FACTORS INFLUENCING THE EFFECTIVENESS OF SECONDARY SCHOOLS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA IN THE NORTHEAST - Pakdeephundon, Pattaranit; Choeybal, Panayuth; Sroinam, Somkid (Journal of Education and Innovation, 2025)
This research has three objectives: 1) to study the effectiveness of secondary schools and the factors influencing their effectiveness in secondary school under the Office of Secondary Educational Service Area in the Northeast; 2) to examine the consistency of the developed causal relationship model with empirical data; and 3) to investigate the direct, indirect, and total influences of factors affecting school effectiveness. The sample consisted of 572 school directors, calculated using G*Power3 and randomly selected in proportion to the population of each school using a lottery method. The findings of this research indicate that 1) the overall effectiveness of secondary schools and the influencing factors have a high average level; 2) the model of factors influencing the effectiveness of secondary schools is consistent with empirical data; 3) the direct influences are ranked as follows: teacher characteristics (0.45), internal atmosphere (0.41), leadership of administrators (0.01), and organizational culture (0.01). The indirect influences are ranked as follows: leadership of administrators (0.71), teacher characteristics (0.14), organizational culture (0.13), and internal atmosphere (0.08). The total influences are ranked as follows: leadership of administrators (0.72), internal atmosphere (0.58), teacher characteristics (0.49), and organizational culture (0.15).